Korelasi Minat dan Motivasi Belajar dengan Hasil Belajar Tematik Kelas V SDN 17 Pontianak Kota - Iwan Suntoso; Suparjan Suparjan; Rio Pranata (ISLAMIKA, 2023)
This study aims to determine whether there is a relationship between learning interest and learning motivation with students' cognitive learning outcomes. Descriptive method in the form of correlation study is used for research. 30 grade V A students at SDN 17 Pontianak City were used as research subjects. The indicators of interest and motivation to learn included: concentration of attention, feeling happy with learning, willingness or tendency to learn, length of study, learning attitude, consistency with learning, persistence with learning, loyalty with learning, and vision with learning. Documents that contain learning outcomes and data from the results of the questionnaire are the statistics used. The data collection technique used was a documentation technique using the average value of thematic cognitive learning of class V A students at SDN 17 Pontianak City, and the data collection method used was an indirect communication technique or an intermediary tool in the form of a learning interest questionnaire and a learning motivation questionnaire using a level significant 5%, or N = 30 is 0.361. This study shows that there is no correlation between students' learning interest and cognitive learning outcomes and the correlation between students' learning motivation and cognitive learning outcomes is rcount = 0.187 and 0.209. As well as interest and student motivation with cognitive learning outcomes is rcount = 0.226. Based on the data obtained, it can be concluded that there is a low correlation between interest and learning motivation with cognitive learning outcomes of students in thematic learning in class V A SDN 17 Pontianak City.